Enhancer-promoter interaction facilitated by transiently forming G-quadruplexes - Hegyi, Hedi (Scientific reports, 2015)
G-quadruplexes are guanine-rich nucleic acid sequences capable of forming a four-stranded structure through Hoogsteen hydrogen bonding. G-quadruplexes are highly concentrated near promoters and transcription start sites suggesting a role in gene regulation. They are less often found on the template than non-template strand where they either inhibit or enhance transcription, respectively. However, their potential role in enhancers and other distal regulatory elements has not been assessed yet. Here we show that DNAse hypersensitive (DHS) cis-regulatory elements are also enriched in Gs and their G-content correlate with that of their respective promoters. Besides local G4s, the distal cis regions may form G-quadruplexes together with the promoters, each contributing half a G4. This model is supported more for the non-template strand and we hypothesised that the G4 forming capability of the promoter and the enhancer non-template strand could facilitate their binding together and making the DHS regions accessible for the transcription factory.
Keywords: zastoupení bazí; Protein Binding; regulační oblasti nukleových kyselin; vazebná místa; Guanine; promotorové oblasti (genetika); G-Quadruplexes; Models, Biological; zesilovače transkripce; vazba proteinů; Binding Sites; lidé; Enhancer Elements, Genetic; biologické modely; Transcription Factors; transkripční faktory; Humans; Base Composition; Promoter Regions, Genetic; Regulatory Sequences, Nucleic Acid; G-kvadruplexy; guanin